Partial versus complete prostatectomy specimen sampling: prospective non-inferiority study for pT3a tumours and surgical margin involvement - Mike Kliffen; Eelco R P Collette; Michael A den Bakker; Sjoerd O Klaver; André N Vis (BMJ Open)
Aims The importance of additional information gained by complete versus partial sampling or prostatectomy specimens is uncertain. There is sparse data on the value of complete versus partial sampling and numbers of inclusions in studies are small and retrospective. We present the results of a prospective non-inferiority study to examine if partial sampling is inferior to complete sampling in terms of pathology outcomes and clinical relevance.Methods 564 robot-assisted prostatectomy (RARP) specimens with prospective registration and analysis were collected over a 2-year period. All patients underwent RARP between January 2014 and February 2016 in our hospital after a diagnosis of clinically localised prostate cancer. For each patient, tumour stage and surgical margin status was recorded after partial and after complete sampling. Upstaging from pT2 to pT3a and upgrading from a negative-to-positive surgical margin was analysed.Results In 12 of 564 patients (2.1%), complete sampling yielded new information. In eight patients (1.4%), the surgical margin converted to positive after complete sampling. Upstaging from initial pT2 tumour in partial sampling to pT3a tumour after complete sampling was documented in five patients (0.9%). In the follow-up period (mean 35 months), a biochemical recurrence occurred in one patient.Conclusions Complete sampling provides new information in only 2.1% of cases, compared with partial sampling. We conclude that the additional information gained by complete sampling in terms of stage and surgical margin detection is statistically insignificant compared with partial sampling. Furthermore, partial sampling compared with complete sampling does not change postoperative clinical management.